REVOLUTIONIZING EDUCATION: UNVEILING THE GAME-CHANGING HYBRID LEARNING STRATEGIES OF FUTURE EDUCATORS - Khabib, Samsul; Indrayanti, Tri; Salsabilah, Adam Romy (FKIP Unismuh Makassar, 2023)
This study investigated the challenges prospective professional teachers face in implementing hybrid learning in their future classrooms. It explores the potential of hybrid learning, which combines online and in-person instruction, to revolutionize traditional education. The research involved 21 students from a private university in Surabaya, Indonesia, who participated in the Teacher Professional Development program. Data were collected through questionnaires and interviews to gain insights into the participants' experiences and perspectives. A comprehensive analysis using both quantitative (descriptive statistics and inferential analysis) and qualitative (thematic analysis) methods identified key strategies for effectively implementing and carrying out hybrid learning. The findings highlight the importance of enhancing students' and teachers' learning competence, explaining the course structure, properly preparing and delivering lessons, and obtaining support from various stakeholders. Additionally, the study outlines the responsibilities of teachers in designing and delivering best-practice hybrid courses and emphasizes the essential support and policy obligations of educational institutions. This study fills a significant gap in implementing hybrid learning in education, providing valuable insights for future educational practices.